CO2 capture initiatives: are governments, society, industry and the financial sector ready?. (December 2022) - Perreault, Patrice; Kummamuru, Nithin B; Gonzalez Quiroga, Arturo; Lenaerts, Silvia
Abstract : The deployment of CCUS plants does not match the enormous requirements to meet the CO2 emission reductions fixed during the Paris agreement, and we must ask ourselves what is refraining the technology deployment, especially in light of the recent high CO2 prices. Owing to the higher costs than their fossil counterparts, Carbon Capture & Utilization represents a long-term solution. In addition to a gigantic scale-up effort even for the most mature Carbon Capture & Storage (CCS) technologies, various factors are responsible for the slow roll-out of CCS projects. Luckily, the financial sector and governments are playing their role. Support from the public is however key, and an open communication is required to convert social tolerance into social acceptance. Highlights: CCS project roll-out does not match the Paris Agreement requirements. Support from the financial sector, public and government, is key for CCS deployment. The cost of CCS projects is a major hurdle, and only two CCS techniques are mature. Social acceptance and public support is key for the successful deployment.